STRATEGI GURU IPS DALAM INTERNALISASI NILAI-NILAI MORAL SISWA DI SMP NUSANTARA MAKASSAR - Hasni Hasni; Herman Herman; Ibrahim Ibrahim (Indonesian Journal of Educational Studies, 2017)
This study aims to determine the strategy of planting a social studies teacher in the internalization of moral values of students in junior archipelago Makassar, and factors internalization planting moral values of students in junior archipelago Makassar. The data has been collected, both primary data and secondary data were analyzed qualitatively and hereinafter described. The results showed that (1) Strategy Master IPS Investment In Internalization of Moral Values Students in junior archipelago Makassar using strategies bervarisi that preventive strategies, repressive strategies and curative strategies. (2) Factors Internalization Planting Moral Values of students in junior archipelago Makassar are no factors supporting and inhibiting factors, and supporting factors of internalizing planting moral values of students in social studies is on the teachers themselves, parents and in the student's own, while the inhibiting factor of intrenalisasi planting moral values of students in social studies is the environmental factor family, peers and the factors advanced communication tools.